Relationship Between Self-Compassion (Welas Diri) and Perceived Stress Parents with Speech Delay Children - Aufa Rizqia Sahna; Nadya Ariyani Hasanah Nuriyyatiningrum; Reti Wahyuni (Seurune : Jurnal Psikologi Unsyiah, 2025)
Speech delay in children can present significant challenges for parents, often having a detrimental effect on their psychological well-being. This is partly due to the numerous negative stigmas that are still firmly associated with children with special needs, including speech delay. Parents of children with speech delay are more likely to experience elevated levels of stress due to the presence of more complex parenting challenges in comparison to parents of children with other special needs. Prolonged exposure to stress without adequate management can give to maladaptive coping strategies. This study aims to examine the relationship between self-compassion and perceived stress in parents with children who have speech delay disorders. A correlational quantitative approach was adopted in this research, with a total of 50 parents who have children with speech delay serving as respondents. The resulting data was analyzed using Spearman's rho correlation test with a value of p0.05, which indicates that the hypothesis in this research is accepted. The correlation coefficient value obtained was r = -0.681. The obtained value indicates a negative correlation, suggesting that as self-compassion among parents of children with speech disorders increases, their stress levels decrease.Abstrak: Kondisi speech delay pada anak dapat menimbulkan tantangan yang besar dan seringkali mempengaruhi kesejahteraan psikologis para orang tua, sebab banyaknya stigma negatif yang masih melekat kuat terkait anak-anak dengan gangguan khusus, salah satunya ialah keterlambatan wicara (speech delay). Orang tua dengan anak yang mengalami keterlambatan bicara rentan terhadap stres sebab dihadapkan dengan tantangan pengasuhan yang lebih kompleks dibanding orangtua dengan anak berkebutuhan khusus lainnya. Stres yang tidak ditangani dengan baik dapat menyebabkan strategi coping yang maladaptif. Sehingga penelitian ini bertujuan untuk melihat apakah terdapat hubungan antara sikap welas diri dengan perceived stress yang dimiliki orang tua yang memiliki anak dengan gangguan keterlambatan bicara. Pendekatan kuantitatif korelasional digunakan dalam riset ini, dengan jumlah responden 50 orang tua yang memiliki anak dengan keterlambatan bicara. Data yang dihasilkan kemudian dianalisis menggunakan uji korelasi Spearmans rho dengan nilai p0.05, yang mengindikasikan hipotesis dalam riset ini diterima. Serta nilai koefisiensi korelasi yang didapatkan r = -0.681. Arah korelasi negatif didapatkan sehingga semakin tinggi sikap welas diri yang dimiliki orang tua yang memiliki anak dengan gangguan wicara maka semakin rendah tingkat stres yang dirasakan.